Co-delivery of anti-PLK-1 siRNA and camptothecin by nanometric polydiacetylenic micelles results in a synergistic cell killing. Issue 37 (6th June 2018) - Ripoll, Manon; Pierdant, Marie; Neuberg, Patrick; Bagnard, Dominique; Wagner, Alain; Kichler, Antoine; Remy, Jean-Serge
Abstract : Recently, it has been shown that the efficiency of antitumoral drugs can be enhanced when combined with therapeutic siRNAs. Abstract : Recently, it has been shown that the efficiency of antitumoral drugs can be enhanced when combined with therapeutic siRNAs. In the present study, an original platform based on polydiacetylenic micelles containing a cationic head group able to efficiently deliver a small interfering RNA (siRNA) targeting the PLK-1 gene while offering a hydrophobic environment for encapsulation of lipophilic drugs such as camptothecin is developed. We demonstrate that the co-delivery of these two agents with our micellar system results in a synergistic tumor cell killing of cervical and breast cancer cell lines in vitro . The combined drugs are active in a subcutaneous in vivo cancer model. Altogether, the results show that our nanometric micellar delivery system can be used for the development of new drug–siRNA combo-therapies.